1974
DOI: 10.1104/pp.53.3.445
|View full text |Cite
|
Sign up to set email alerts
|

Red Light Enhancement of the Phototropic Response of Etiolated Pea Stems

Abstract: In the subapical third internode of 7-day-old etiolated pea seedlings, the magnitude of phototropic curvature in response to continuous unilateral blue illumination is increased when seedlings are pre-exposed to brief red light. The effect of red light on blue light-induced phototropism becomes manifest maximally 4 or more hours after red illumination, and closely parallels the promotive action of red light on the elongation of the subapical cells. Ethylene inhibits phototropic curvature by an inhibitory actio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
17
0

Year Published

1976
1976
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…Although they were not able to completely exclude a role for light-mediated inhibition of polar auxin transport, their results further demonstrated that unilateral blue light induced lateral auxin transport. At the same time, Kang and Burg (1974) reported that the enhancement of pea epicotyl phototropism by red light or gibberellins did not correlate with an increase in lateral auxin transport and proposed that the magnitude of the phototropic response is determined by adjusting auxin sensitivity. Altogether, these studies supported the involvement of auxin in phototropism, but the precise mechanism of how auxin transport and signaling cause phototropism remained unknown.…”
Section: The Discovery Of Auxin and Understanding Its Role In Phototrmentioning
confidence: 99%
“…Although they were not able to completely exclude a role for light-mediated inhibition of polar auxin transport, their results further demonstrated that unilateral blue light induced lateral auxin transport. At the same time, Kang and Burg (1974) reported that the enhancement of pea epicotyl phototropism by red light or gibberellins did not correlate with an increase in lateral auxin transport and proposed that the magnitude of the phototropic response is determined by adjusting auxin sensitivity. Altogether, these studies supported the involvement of auxin in phototropism, but the precise mechanism of how auxin transport and signaling cause phototropism remained unknown.…”
Section: The Discovery Of Auxin and Understanding Its Role In Phototrmentioning
confidence: 99%
“…The mechanism through which this suppression occurs is unknown, although it is probable that blue light affects the yielding properties of the cell wall, and not the hydraulic conductivity of the growing tissue (9). The biochemical signal for the blue light-induced suppression of growth may involve auxin flow as is proposed for phototropic curvature (3,5,16,19). This latter effect of blue light is thought to occur as a result of the lateral redistribution of auxin away from the irradiated side of the plant resulting in a lessened rate of growth on the irradiated side (5).…”
mentioning
confidence: 99%
“…Of these hormones, auxin and ethylene demonstrably control or modify phototropism (Harper et al, 2000), and other reports indicate that gibberellins (Phillips, 1972;Kang and Burg, 1974) might also influence the response. In a review citing unpublished results, Briggs and Liscum (1997) suggested that the nph5 mutants, which are reportedly allelic to amp1/cop2, have diminished gravitropism and phototropic responses.…”
mentioning
confidence: 99%